The importance of artistic and aesthetic education of youth (case of additional education establishments of Nizhny Novgorod) - Nemova, Olga; Kazantseva, Galina; Karpukova, Albina; Sizova, Olga; Medvedeva, Tatiana; Retivina, Veronika (International Journal of Psychosocial Rehabilitation, 2020)
The article gives an overview of the system of additional education in Nizhny Novgorod, which provides artistic and aesthetic education services for the younger generation. The importance of developing a system of cultural values in children is shown. Statistical data on the state of the system of additional education in Nizhny Novgorod is provided. The authors present the results of a sociological study of parents’ satisfaction with provided educational services. Parents showed a high level of satisfaction with the quality of the additional educational services provided in the city. Conclusions are drawn about the importance of additional education in the process of artistic and aesthetic education.